Pelatihan Dan Pembuatan Pupur Babigi Gelinggang Kelor Bersama Ibu – Ibu Di Desa Kalahang Kabupaten Tabalong - Firda Herlina; Robiatul Adawiah; Ice Trianiza; Yuli Panca; Agus Wiramsya Oscar; Faisal Rahman; Hazairin; Jainal Arifin; Mujiburahman (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Indonesia has abundant biodiversity, yet its utilization is still limited to traditional consumption and has not been widely developed into economically valuable products. The leaves of galingale (Cassia alata) contain flavonoids, alkaloids, and tannins that are beneficial as antibacterials and antifungals, while the moringa leaves (Moringa oleifera) are rich in antioxidants, vitamins, and minerals beneficial for skin health. One local wisdom of the Kalimantan community is the pupur babigi, a traditional powder made from natural ingredients, which is now being abandoned due to the influx of modern cosmetic products. This community service activity aims to: (1) increase public knowledge about the contents and benefits of galingale and moringa leaves, (2) train the community in making pupur babigi, and (3) encourage the creation of micro-enterprises based on herbal products. The methods include preparation, socialization, practical training, mentoring, and evaluation, involving 25 participants (housewives and youth from the community). The results show an increase in participants' understanding from 20% (pre-training) to 85% (post-training). All participants were able to produce pupur babigi of good quality, and 80% expressed interest in developing the product as a business. In addition to skills transfer, this activity also raised collective awareness about the importance of utilizing local natural resources for economic empowerment.